Effects of Student Self-Assessment and Using GeoGebra™ on Students’ Achievements and Self-Directed Learning in Mathematics Lessons in a Junior High Classroom - Phoodee, Wuttichai (Southeast Asian Mathematics Education Journal, 2023)
This paper demonstrates a teacher-as-researcher intervention study of Student Self-Assessment, utilizing  GeoGebra  activities on  the topic of relationships of geometric figures. The teacher researcher studied students’ achievements and self-directed learning by including Student Self-Assessment (SSA) and by teaching procedural knowledge and conceptual knowledge using eleven GeoGebra-based tasks at the same time. The data were collected via questionnaire,  interview, as well  as two  tests  which  were  given  after  task 6 and  task  11 were  completed. The  teacher  researcher  oversaw  the  progress  of  the 24 Thai male and female junior high mathematics students  (13-14  years old), and offered prompt guidance and support using normal  classroom techniques.The  findings  indicated  that  the utilization  of SSA and  GeoGebra  had  a  positive  impact  on  these  students'  academic performance  and  their  ability  to  take  charge  of  their  learning  in  mathematics classes. Specifically,  the  intervention  led  to 1) improved communication between student and teacher;  2) improved students’ understanding of what they needed to  learn;  3) improved students’ confidence to ask for help from the teacher;  4) promoted student  achievement; and 5) promoted self-directed learning in mathematics lessons.